Elevating Shariah Hotel Hospitality: Secrets to Guest Satisfaction and Loyalty in Indonesia - Andhi Sukma; Maria Rochelle G Divinagracia; Louie A Divinagracia (Faculty of Economic and Business, 2024)
Research Originality: This research highlights the importance of personalized services, organizational image, and effective customer relationship management (CRM) strategies aligned with Islamic principles. The research aims to distinguish shariah hospitality and deepen understanding of customer behavior in this cultural and religious context.Research Objectives: This study examines how personalized services, company image (CI) and customer perceived value (CPV) affect guest satisfaction and loyalty in Shariah-based hotels, providing insights into customer behavior.Research Methods: The review analyzed customer relationship management, organization picture, and perceived value as independent factors, with loyalty as the dependent variable and satisfaction as the mediator. Data came from 220 guests at Shariah hotels in Indonesia.Empirical Results: The study found strong links between personalized services, a positive organization picture, and perceived value with guest satisfaction and loyalty in Shariah-based hotels, emphasizing the need for effective CRM, a robust brand, and high-quality service.Implications: This research advances customer relationship management (CRM) and Customer Perceived Value (CPV) theories in Shariah hotels through personalized services, effective communication, and strong branding, guiding hotels to prioritize these strategies for customer loyalty in hospitality. JEL Classification: L83, M31, M39How to Cite:Sukma, A., Divinagracia, M. R. G., Divinagracia, L. A. (2024). The Path to Guest Satisfaction: Leveraging Personalized Services and Islamic Principles in Shariah Hospitality. Etikonomi, 23(2), 449 – 464. https://doi.org/10.15408/etk.v23i1.38502.